Environment-friendly structural adhesive as well as preparation method and application thereof

By using bio-based materials such as epoxy resin and waste aluminum tailings mud powder, combining bio-flame retardant and chemical flame retardant, the components and proportions of structural glue are optimized, and the permeability and bonding of existing structural glues are solved. The problem of difficulty in balancing strength has achieved efficient, environmentally friendly and low-cost structural adhesive performance improvement.

CN119432287APending Publication Date: 2025-02-14GUANGXI UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411687659.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing structural glue is difficult to balance between permeability and bonding strength, and the components are mostly chemical materials, which poses the risk of polluting the environment and endangering human health, is insufficient flammability, and improper proportioning leads to insufficient mechanical properties.

Method used

Using components such as epoxy resin, biodiluent, biotoughening agent, bioflame retardant and waste aluminum tailings mud powder, the ratio of diluent and toughening agent is reasonably designed, combining bioflame retardant and chemical flame retardant optimize the ratio of structural glue and aggregate.

Benefits of technology

A good compromise between the permeability and bonding strength of structural glue is achieved, which reduces the harm to the environment and human health, improves flame retardant and mechanical properties, and has lower costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides an environment-friendly structural adhesive which comprises a component A and a component B. The component A comprises the following components in parts by weight: 100 parts of epoxy resin, 30-50 parts of a diluent, 13-30 parts of a flexibilizer, 10-25 parts of a flame retardant and 3-10 parts of waste aluminum tailing slurry powder. The component B comprises the following components in parts by weight: 80-86 parts of phenolic aldehyde amine, 4-8 parts of a 593 curing agent, 4-12 parts of polyether amine and 2-8 parts of N-aminoethyl piperazine; the structural adhesive not only can reduce the risk of harming human health and polluting ecological environment, but also has good permeability, bonding strength and flame retardance, and is suitable for large-scale popularization and application. The structural adhesive provided by the invention is simple in preparation method, relatively low in cost and suitable for large-scale popularization and application. The structural adhesive is applied to preparation of the structural adhesive concrete, the provided proportion is reasonable and simple, and the problem that traditional cement concrete is insufficient in tensile strength and compressive strength is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete structural adhesive, and in particular to an environmentally friendly structural adhesive and a preparation method and application thereof. Background Art

[0002] Cement concrete occupies a prominent position in the field of civil engineering due to its excellent compressive strength and economy, and has become one of the most consumed building materials in the world. However, its relatively low tensile properties and limited bonding properties have restricted its practical scope to a certain extent. Therefore, polymer concrete, as a potential substitute for traditional cement concrete, has gradually become a new research hotspot in recent years. Unlike cement concrete, which uses cement and aggregate to mix, polymer concrete uses structural adhesive to mix with aggregate. Since structural adhesive provides higher bonding strength and resistance to salt erosion for concrete, polymer concrete has stronger tensile strength, bonding strength and durability.

[0003] However, when the existing traditional structural adhesive is mixed with aggregate, there are several problems to be solved:

[0004] (1) It is difficult to strike a balance between permeability and bond strength, resulting in poor strength and durability of structural adhesive concrete. On the one hand, the aggregate contains fillers and coarse aggregates. In order to fully mix all the aggregates, the structural adhesive needs to have good permeability to completely wrap the fillers and penetrate into the gaps in the coarse aggregates. On the other hand, the structural adhesive also needs to have sufficient bond strength so that the polymer concrete has sufficient strength after curing. However, the permeability and bond strength of structural adhesives are usually difficult to balance. To obtain better permeability, it is necessary to add a certain amount of diluent, which often leads to a decrease in the bond strength of the structural adhesive. Therefore, between the two properties of permeability and bond strength, it is usually necessary to sacrifice one of the properties to obtain the other. How to strike a good balance between the two is the key to improving the practicality of structural adhesives for concrete.

[0005] (2) Traditional structural adhesives are mostly composed of chemical materials. For example, diluents usually use highly toxic furfural-acetone diluents. Not only do they pollute the environment and harm human health during production and use, but the production process of raw materials also produces a large amount of greenhouse gases such as carbon dioxide. Therefore, the development of structural adhesives based on bio-based materials is of great significance to reduce the risk of structural adhesive concrete pollution and improve the sustainable development of the civil engineering industry.

[0006] (3) Flammability is a material defect of structural adhesives themselves, which will seriously affect the safety and fire resistance of structural adhesive concrete. The common method to improve the fire resistance of structural adhesives is to add flame retardants, but the type and dosage of flame retardants need to be properly controlled to ensure other properties while improving flame retardancy. In addition, once traditional industrial flame retardants are burned, they will produce a large amount of toxic gases, which will harm human health and the ecological environment. Therefore, using bio-flame retardants to partially replace traditional industrial flame retardants will help improve the environmental protection characteristics of structural adhesives.

[0007] (4) Improper ratio of structural adhesive to aggregate is an important factor in the insufficient mechanical properties of structural adhesive concrete. When the amount of structural adhesive is too small, the aggregate cannot be completely wrapped, and the structural adhesive and aggregate cannot play their respective roles effectively; when the amount of structural adhesive is too large, on the one hand, it wastes materials, and on the other hand, it will lead to an uncoordinated overall force system of the structure and low bearing capacity. In addition, the size of the aggregate also has an important influence on the performance of structural adhesive concrete. Therefore, a reasonable ratio is also an important factor in ensuring the performance of structural adhesive concrete.

[0008] In summary, it is hoped to provide an environmentally friendly structural adhesive that can reduce the risk of harming human health and polluting the ecological environment, and has good permeability, bonding strength and flame retardancy. Summary of the invention

[0009] In order to overcome the above-mentioned deficiencies of the prior art, the first object of the present invention is to provide an environmentally friendly structural adhesive, which can not only reduce the risks of harming human health and polluting the ecological environment, but also has good permeability, bonding strength and flame retardancy, and is suitable for large-scale promotion and application.

[0010] The second object of the present invention is to provide a method for preparing an environmentally friendly structural adhesive, which has a simple design, low cost and is suitable for large-scale promotion and application.

[0011] The third object of the present invention is to provide an application of an environmentally friendly structural adhesive, which provides a reasonable and simple ratio and solves the problem of insufficient tensile strength and compressive strength of traditional cement concrete.

[0012] In order to achieve the above object, in a first aspect of the present invention, an environmentally friendly structural adhesive is provided, which comprises a component A and a component B; preferably, the weight ratio of component A to component B is 1 to 1.2:1;

[0013] The A component comprises the following components in parts by weight:

[0014] Epoxy resin 100 parts,

[0015] 30-50 parts of diluent,

[0016] 13 to 30 parts of toughening agent,

[0017] Flame retardant 10-25 parts,

[0018] 3 to 10 parts of waste aluminum tailings slurry powder;

[0019] The epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and bisphenol S epoxy resin;

[0020] Bisphenol A epoxy resin can be a commercially available product, such as the epoxy resin model 601 of Laizhou Baichen Insulation Material Co., Ltd.; bisphenol F epoxy resin can be a commercially available product, such as the epoxy resin model 170 of Jining Hongming Chemical Reagent Co., Ltd.; bisphenol S epoxy resin can be a commercially available product, such as the epoxy resin model 185S of Jiangsu Aolunda Technology Industry Co., Ltd.;

[0021] The diluent is a biological diluent;

[0022] The biodiluent is one or both of palmitic acid glycerol and poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid);

[0023] Palmitic acid glyceryl ester can be a commercially available product, such as palmitic acid glyceryl ester with model number 1716-07-0 from Shanghai Huicheng Biotechnology Co., Ltd.; 3-hydroxybutyric acid-co-3-hydroxyvaleric acid can be a commercially available product, such as 3-hydroxybutyric acid-co-3-hydroxyvaleric acid with model number 80181-31-3 from Hubei Enxing Biotechnology Co., Ltd.;

[0024] The toughening agent is a biological toughening agent;

[0025] The biological toughening agent is one or both of polylactic acid and polyhydroxyalkanoate;

[0026] The polylactic acid may be a commercially available product, such as the polylactic acid model 26100-51-6 produced by Shanghai Yuanye Biotechnology Co., Ltd.; the polyhydroxyalkanoate may be a commercially available product, such as the polyhydroxyalkanoate model RT029 produced by Shanghai Yuanye Biotechnology Co., Ltd.;

[0027] The flame retardant is composed of a biological flame retardant and a chemical flame retardant, and preferably, the weight ratio of the biological flame retardant to the chemical flame retardant is 1:1;

[0028] The biological flame retardant is tea polyphenols;

[0029] Tea polyphenols can be commercially available products, such as tea polyphenols with model number 27073-41-2 from Shanghai Yuanye Biotechnology Co., Ltd.;

[0030] The chemical flame retardant is 4,4'-diaminodiphenylmethane;

[0031] 4,4'-diaminodiphenylmethane can be a commercially available product, such as 4,4'-diaminodiphenylmethane model 4010NA from Jinan Xinhou Trading Co., Ltd.;

[0032] The preparation of the waste aluminum tailings slurry powder comprises the following steps:

[0033] (1) Take the waste tailings slurry discharged from the aluminum ore dressing and washing workshop;

[0034] (2) Add polyaluminium chloride and stir;

[0035] (3) adding sodium polyacrylate, stirring, and then letting stand;

[0036] (4) Pour off the excess water on the top and spread the mud evenly;

[0037] (5) placing the mud in an oven for drying;

[0038] (6) fully grinding the dried mud, and then filtering it through a 0.075 mm sieve to prepare waste aluminum tailings mud powder;

[0039] Preferably, the waste tailings slurry has a mud content of 7wt% to 20wt%, and the volume ratio of the waste tailings slurry, polyaluminium chloride and sodium polyacrylate is 800:1:2;

[0040] Preferably, the stirring time in step (2) is 5 minutes; the stirring time in step (3) is 5 minutes; the standing time is 10 minutes; the temperature in the oven in step (6) is set to 60° C. and the drying is performed for at least 2 hours;

[0041] The B component comprises the following components in parts by weight:

[0042] 80-86 parts of phenalkamine,

[0043] 593 curing agent 4-8 parts,

[0044] 4-12 parts of polyetheramine,

[0045] 2 to 8 parts of N-aminoethylpiperazine;

[0046] Phenolic amine can be a commercially available product, such as NC541 phenolic amine produced by Guangzhou Weilina Chemical Co., Ltd.;

[0047] The 593 curing agent is a fatty amine-epoxy resin addition product, and the curing agent model 593 of Guangzhou Jiana Chemical Co., Ltd. can be used;

[0048] The polyetheramine can be a commercially available product, such as the polyetheramine model D230 produced by Shandong Rongwei Chemical Co., Ltd.;

[0049] N-aminoethylpiperazine can be a commercially available product, such as N-aminoethylpiperazine with model number 140-31-8 produced by Nanjing Oriental Pearl Industry and Trade Co., Ltd.

[0050] In a second aspect of the present invention, a method for preparing the above-mentioned environmentally friendly structural adhesive is provided, characterized in that it comprises:

[0051] The preparation of component A comprises the following steps:

[0052] S1. At room temperature, mix the liquid epoxy resin with the diluent and shear;

[0053] S2. Add toughening agent and flame retardant, shear;

[0054] S3. Add the waste aluminum tailings slurry powder, shear, then disperse, and finally evacuate to obtain component A;

[0055] Preferably, the shearing time in step S1 is 35 min; the shearing time in step S2 is 35 min; the shearing time in step S3 is 25 min, the dispersion time in step S3 is 50 min, and the vacuuming time in step S3 is 7 min.

[0056] The shearing is carried out in a high-speed shearing machine, which is a conventional equipment, such as the SRS500 high-speed shearing machine of Shanghai Xinle Electromechanical Technology Co., Ltd.; the dispersion is carried out in an ultrasonic disperser, which is a conventional equipment, such as the rps-20k 500W ultrasonic disperser of Hangzhou Gonglv Ultrasonic Equipment Co., Ltd.; the vacuuming is carried out in a vacuum centrifugal concentrator, which is a conventional equipment, such as the SZL3-3K vacuum centrifugal concentrator of Shenzhen Sanli Technology Co., Ltd.

[0057] Preparation of component B: phenolic amine, 593 curing agent, polyether amine and N-aminoethyl piperazine are mixed and dispersed to obtain component B.

[0058] Preparation of environmentally friendly structural adhesive: Mix and disperse component A and component B to obtain an environmentally friendly structural adhesive.

[0059] In the third aspect of the present invention, the above-mentioned environmentally friendly structural adhesive is used to prepare structural adhesive concrete, including: the environmentally friendly structural adhesive and the filler are mixed evenly to form a cementitious material, and then the cementitious material and the coarse aggregate are mixed evenly to form structural adhesive concrete; the weight ratio of the environmentally friendly structural adhesive to the filler is 7:3; the particle range of the filler is 20 to 100 μm; the weight ratio of the cementitious material to the coarse aggregate is 1:1.3; the nominal particle size of the coarse aggregate is 5 mm.

[0060] Preferably, the filler is one or both of limestone powder and fly ash; and the coarse aggregate is quartz stone.

[0061] Preferably, the stirring time is 5 min.

[0062] The present invention has the following beneficial effects:

[0063] (1) Through the reasonable design of the diluent and the toughening agent, the structural adhesive of the present invention achieves a good compromise between permeability and bonding strength, avoiding the performance imbalance problem caused by being too thin or too tough, thereby significantly improving the practicality of the structural adhesive as a concrete binder.

[0064] (2) The structural adhesive of the present invention uses a variety of biomaterials or waste materials to partially replace traditional chemical materials. These alternative materials are non-toxic and harmless during the production process, do not produce greenhouse gases such as carbon dioxide, and can be decomposed by microorganisms during the application process. They will not have long-term impact on the environment, fully embodying the concept of sustainable and low-carbon development.

[0065] (3) The structural adhesive of the present invention utilizes a clever combination of biological flame retardants and chemical flame retardants to provide a highly efficient flame retardant effect while reducing the impact on the ecological environment.

[0066] (4) The structural adhesive of the present invention fully exerts the performance of each component through the optimized design of the ratio of filler and coarse aggregate, and prepares structural adhesive concrete with high tensile strength and anti-tensile strength. Compared with structural adhesive concrete with other ratios or traditional structural adhesive concrete, it has better performance and lower cost. DETAILED DESCRIPTION

[0067] The present invention is further described below in conjunction with specific preferred embodiments, but the protection scope of the present invention is not limited thereby.

[0068] Embodiment 1 to Embodiment 5

[0069] Use the formula shown in Table 1

[0070] The preparation method is as follows:

[0071] Preparation of component A:

[0072] (1) At room temperature, liquid epoxy resin and diluent are mixed and sheared for 35 minutes;

[0073] (2) Add toughening agent and flame retardant, shear, and the shearing time is 35 minutes;

[0074] (3) Add the waste aluminum tailings slurry powder, shear for 25 minutes, disperse for 50 minutes, and finally vacuum for 7 minutes to obtain component A.

[0075] The shearing is carried out in a high-speed shearing machine, which is a conventional equipment, and is a high-speed shearing machine model SRS500 produced by Shanghai Xinle Electromechanical Technology Co., Ltd.; the dispersion is carried out in an ultrasonic disperser, which is a conventional equipment, and is a rps-20k 500W ultrasonic disperser produced by Hangzhou Gonglu Ultrasonic Equipment Co., Ltd.; the vacuuming is carried out in a vacuum centrifugal concentrator, which is a conventional equipment, and is a vacuum centrifugal concentrator model SZL3-3K produced by Shenzhen Sanli Technology Co., Ltd.

[0076] Preparation of waste aluminum tailings slurry powder:

[0077] (1) In a 1000 mL measuring cylinder, pour 800 mL of waste tailings slurry with a mud content of 12 wt% discharged from an aluminum ore dressing and washing workshop;

[0078] (2) Pour 1 mL of polyaluminium chloride and stir for 5 min;

[0079] (3) Pour in 2 mL of sodium polyacrylate, stir for 5 min, and then let stand for 10 min;

[0080] (4) Pour off the excess water in the upper part of the measuring cylinder and pour the precipitated mud in the lower part into a tray of 30 cm × 40 cm × 4 cm and spread it evenly;

[0081] (5) Place the tray in a 60°C oven and dry for 2 hours;

[0082] (6) The dried mud is fully ground and then filtered through a 0.075 mm sieve to prepare waste aluminum tailings mud powder.

[0083] Preparation of component B:

[0084] Component B can be obtained by mixing and dispersing phenolic amine, 593 curing agent, polyether amine and N-aminoethyl piperazine.

[0085] Preparation of environmentally friendly structural adhesive: Component A and component B are mixed and dispersed in a weight ratio of component A to component B of 1:1 to obtain an environmentally friendly structural adhesive.

[0086] The epoxy resin used in Example 1 is bisphenol A epoxy resin;

[0087] The epoxy resin used in Example 2 is bisphenol F epoxy resin;

[0088] The epoxy resin used in Example 3 is bisphenol S epoxy resin;

[0089] The epoxy resin used in Example 4 is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, with a weight ratio of bisphenol A epoxy resin: bisphenol F epoxy resin = 50:50;

[0090] The epoxy resin used in Example 5 is a mixture of bisphenol F epoxy resin and bisphenol S epoxy resin, with a weight ratio of bisphenol F epoxy resin: bisphenol S epoxy resin = 70:30;

[0091] The diluent used in Example 1 is palmitic acid glyceride;

[0092] The diluent used in Example 2 is palmitic acid glyceride;

[0093] The diluent used in Example 3 is poly(3-hydroxybutyric acid-co-3-hydroxyvaleric acid);

[0094] The diluent used in Example 4 is poly(3-hydroxybutyric acid-co-3-hydroxyvaleric acid);

[0095] The diluent used in Example 5 is a mixture of palmitic acid glycerol and poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid), with a weight ratio of palmitic acid glycerol: poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) = 60:40;

[0096] The toughening agent used in Example 1 is polylactic acid;

[0097] The toughening agent used in Example 2 is polylactic acid;

[0098] The toughening agent used in Example 3 is polyhydroxyalkanoate;

[0099] The toughening agent used in Example 4 is polyhydroxyalkanoate;

[0100] The toughening agent used in Example 5 is a mixture of polylactic acid and polyhydroxyalkanoate, with a weight ratio of polylactic acid: polyhydroxyalkanoate = 30:70;

[0101] Table 1

[0102]

[0103]

[0104] Comparative Example 1 to Comparative Example 5

[0105] Use the formula shown in Table 2

[0106] The preparation method is as follows:

[0107] Preparation of component A:

[0108] (1) At room temperature, liquid epoxy resin and diluent are mixed and sheared for 35 minutes;

[0109] (2) Add toughening agent and flame retardant, shear, and the shearing time is 35 minutes;

[0110] (3) Add the waste aluminum tailings slurry powder, shear for 25 minutes, disperse for 50 minutes, and finally vacuum for 7 minutes to obtain component A.

[0111] The shearing is carried out in a high-speed shearing machine, which is a conventional equipment, and is a high-speed shearing machine model SRS500 produced by Shanghai Xinle Electromechanical Technology Co., Ltd.; the dispersion is carried out in an ultrasonic disperser, which is a conventional equipment, and is a rps-20k 500W ultrasonic disperser produced by Hangzhou Gonglu Ultrasonic Equipment Co., Ltd.; the vacuuming is carried out in a vacuum centrifugal concentrator, which is a conventional equipment, and is a vacuum centrifugal concentrator model SZL3-3K produced by Shenzhen Sanli Technology Co., Ltd.

[0112] Preparation of waste aluminum tailings slurry powder:

[0113] (1) In a 1000 mL measuring cylinder, pour 800 mL of waste tailings slurry with a mud content of 12 wt% discharged from an aluminum ore dressing and washing workshop;

[0114] (2) Pour 1 mL of polyaluminium chloride and stir for 5 min;

[0115] (3) Pour in 2 mL of sodium polyacrylate, stir for 5 min, and then let stand for 10 min;

[0116] (4) Pour off the excess water in the upper part of the measuring cylinder and pour the precipitated mud in the lower part into a tray of 30 cm × 40 cm × 4 cm and spread it evenly;

[0117] (5) Place the tray in a 60°C oven and dry for 2 hours;

[0118] (6) The dried mud is fully ground and then filtered through a 0.075 mm sieve to prepare waste aluminum tailings mud powder.

[0119] Preparation of component B:

[0120] Component B can be obtained by mixing and dispersing phenolic amine, 593 curing agent, polyether amine and N-aminoethyl piperazine.

[0121] Preparation of structural adhesive: Component A and component B are mixed and dispersed in a weight ratio of component A to component B of 1:1 to obtain an environmentally friendly structural adhesive.

[0122] The epoxy resin used in Comparative Example 1 is bisphenol A epoxy resin;

[0123] The epoxy resin used in Comparative Example 2 is bisphenol F type epoxy resin;

[0124] The epoxy resin used in Comparative Example 3 is bisphenol S epoxy resin;

[0125] The epoxy resin used in Comparative Example 4 is a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, with a weight ratio of bisphenol A epoxy resin: bisphenol F epoxy resin = 50:50;

[0126] The epoxy resin used in Comparative Example 5 is a mixture of bisphenol F epoxy resin and bisphenol S epoxy resin, with a weight ratio of bisphenol F epoxy resin: bisphenol S epoxy resin = 70:30;

[0127] The diluent used in Comparative Example 1 is palmitic acid glyceride;

[0128] The diluent used in Comparative Example 2 is palmitic acid glyceride;

[0129] The diluent used in Comparative Example 3 is poly(3-hydroxybutyric acid-co-3-hydroxyvaleric acid);

[0130] The diluent used in Comparative Example 4 is poly(3-hydroxybutyric acid-co-3-hydroxyvaleric acid);

[0131] The diluent used in Comparative Example 5 is a mixture of palmitic acid glycerol and poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid), and the weight ratio is: palmitic acid glycerol: poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) = 60:40;

[0132] The toughening agent used in Comparative Example 1 is polylactic acid;

[0133] The toughening agent used in Comparative Example 2 is polylactic acid;

[0134] The toughening agent used in Comparative Example 3 is polyhydroxyalkanoate;

[0135] The toughening agent used in Comparative Example 4 is polyhydroxyalkanoate;

[0136] The toughening agent used in Comparative Example 5 is a mixture of polylactic acid and polyhydroxyalkanoate, with a weight ratio of polylactic acid: polyhydroxyalkanoate = 30:70;

[0137] Compared with Example 1, Comparative Example 1 does not add the abandoned aluminum tailings slurry powder, and other conditions are the same;

[0138] Compared with Example 2, Comparative Example 2 does not add the abandoned aluminum tailings slurry powder and the flame retardant, and other conditions are the same;

[0139] Compared with Example 3, the diluent and toughening agent in Comparative Example 3 are both lower than the set range, and other conditions are the same;

[0140] Compared with Example 4, the toughening agent in Comparative Example 4 is higher than the set range, and other conditions are the same;

[0141] Compared with Example 5, the diluent in Comparative Example 5 is higher than the set range, and other conditions are the same.

[0142] Table 2

[0143]

[0144]

[0145] Comprehensive performance tests were conducted on Examples 1 to 5 and Comparative Examples 1 to 5, and the results are shown in Table 3. The UL-94 test grade was determined according to GB / T 2408-2021; the viscosity refers to the viscosity of the slurry measured by the single cylinder rotation viscometer method immediately after the two components A and B are evenly mixed, and is determined according to GB / T 2794-2013; the permeability is determined according to JC / T 2217-2014; the operable time is the time from the mixing of the two components A and B slurry until the viscosity reaches 200 mPa·s, and is determined according to GBT2794-2022; and the bonding strength is determined according to DL / T 5150-2017.

[0146] Table 3

[0147]

[0148] It can be seen from Table 3 that the environmentally friendly structural adhesive prepared by the present invention has the advantages of good flame retardancy, high viscosity, strong permeability, ample operating time, high bonding strength, etc.

[0149] Example 6

[0150] Application of structural adhesive

[0151] A total of 10 structural adhesives were used in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 5, and were mixed with fillers and aggregates to prepare 10 structural adhesive concretes. Among them, the filler is fly ash with a particle range of 20 to 100 μm, the coarse aggregate is quartz stone with a nominal particle size of 5 mm, the weight ratio of structural adhesive to filler is: structural adhesive: filler = 7:3, the weight ratio of cementitious material to coarse aggregate is: cementitious material: coarse aggregate = 1:1.3, and the mixing time is 5 min. Each structural adhesive concrete was prepared into 6 cylindrical specimens (diameter 50 mm, height 100 mm), of which 3 specimens were used to test the compressive strength with reference to ASTM C39, and the other 3 specimens were used to test the tensile strength with reference to ASTM C496. The results are shown in Table 4.

[0152] Table 4

[0153] sample Compressive strength(MPa) Tensile strength(MPa) Example 1 40.4 11.9 Example 2 39.2 9.5 Example 3 40.5 10.4 Example 4 43.6 12.6 Example 5 41.7 13.7 Comparative Example 1 27.8 6.5 Comparative Example 2 21.4 4.2 Comparative Example 3 26.9 4.8 Comparative Example 4 30.4 5.4 Comparative Example 5 23.3 4.3

[0154] It can be seen from Table 4 that the structural adhesive concrete prepared using the structural adhesive prepared by the present invention has higher compressive strength and tensile strength, indicating that the structural adhesive of the present invention can effectively penetrate into the filler and coarse aggregate, and form a strong and dense combination with the filler and coarse aggregate, plus the bonding strength of the structural adhesive itself, so that good compressive strength and tensile strength can be obtained after curing.

Claims

1. An environmentally friendly structural adhesive, characterized in that: It includes component A and component B; The A component comprises the following components in parts by weight: Epoxy resin 100 parts, 30-50 parts of diluent, 13 to 30 parts of toughening agent, Flame retardant 10-25 parts, 3 to 10 parts of waste aluminum tailings slurry powder; The epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin and bisphenol S epoxy resin; The diluent is a biological diluent; the biological diluent is one or two of palmitic acid glycerol and poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid); The toughening agent is a biological toughening agent; the biological toughening agent is one or two of polylactic acid and polyhydroxyalkanoate; The flame retardant is composed of a biological flame retardant and a chemical flame retardant; the biological flame retardant is tea polyphenol; the chemical flame retardant is 4,4'-diaminodiphenylmethane; The preparation of the waste aluminum tailings slurry powder comprises the following steps: (1) Take the waste tailings slurry discharged from the aluminum ore dressing and washing workshop; (2) Add polyaluminium chloride and stir; (3) adding sodium polyacrylate, stirring, and then letting stand; (4) Pour off the excess water on the top and spread the mud evenly; (5) placing the mud in an oven for drying; (6) fully grinding the dried mud, and then filtering it through a 0.075 mm sieve to prepare waste aluminum tailings mud powder; The B component comprises the following components in parts by weight: 80-86 parts of phenalkamine, 593 curing agent 4-8 parts, 4-12 parts of polyetheramine, 2 to 8 parts of N-aminoethylpiperazine.

2. The environmentally friendly structural adhesive according to claim 1, characterized in that: The weight ratio of the component A to the component B is 1-1.2:

1.

3. The environmentally friendly structural adhesive according to claim 1, characterized in that: The weight ratio of the biological flame retardant to the chemical flame retardant is 1:1; the mud content of the waste tailings slurry is 7wt% to 20wt%, and the volume ratio of the waste tailings slurry, polyaluminum chloride and sodium polyacrylate is 800:1:

2.

4. The environmentally friendly structural adhesive according to claim 1, characterized in that: The stirring time in step (2) is 5 minutes; the stirring time in step (3) is 5 minutes; the standing time is 10 minutes; the temperature in the oven in step (6) is set to 60° C. and the drying is performed for at least 2 hours.

5. The method for preparing the environmentally friendly structural adhesive according to claim 1, characterized in that: include: The preparation of component A comprises the following steps: S1. At room temperature, mix the liquid epoxy resin with the diluent and shear; S2. Add toughening agent and flame retardant, shear; S3. Add the waste aluminum tailings slurry powder, shear, then disperse, and finally evacuate to obtain component A; Preparation of component B: Mix and disperse phenolic amine, 593 curing agent, polyether amine and N-aminoethyl piperazine to obtain component B; Preparation of environmentally friendly structural adhesive: Mix and disperse component A and component B to obtain an environmentally friendly structural adhesive.

6. The preparation method according to claim 5, characterized in that: The shearing time in step S1 is 35 min; the shearing time in step S2 is 35 min; the shearing time in step S3 is 25 min, the dispersion time in step S3 is 50 min, and the vacuuming time in step S3 is 7 min; the shearing is carried out in a high-speed shearing machine; the dispersion is carried out in an ultrasonic disperser; and the vacuuming is carried out in a vacuum centrifugal concentrator.

7. Use of the environmentally friendly structural adhesive according to claim 1 or the environmentally friendly structural adhesive prepared by the preparation method according to claim 5 in preparing structural adhesive concrete.

8. The use according to claim 7, characterized in that: The environmentally friendly structural adhesive and filler are mixed evenly to form a cementitious material, and the cementitious material and coarse aggregate are mixed evenly to form a structural adhesive concrete; The weight ratio of the environmentally friendly structural adhesive to the filler is 7:3; the particle size of the filler is in the range of 20 to 100 μm; the weight ratio of the cementitious material to the coarse aggregate is 1:1.3; and the nominal particle size of the coarse aggregate is 5 mm.

9. The use according to claim 8, characterized in that: The filler is one or two of limestone powder and fly ash; and the coarse aggregate is quartz stone.

10. The use according to claim 8, characterized in that: The stirring time is 5 min.

Citation Information

Cited By

  • Environment-friendly unsaturated polyester cement mortar and preparation method thereof

    CN120483584A